Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine the value of the expression \(-3mn + 4m - 3\) given that \(m = 2\) and \(n = -4\), follow these steps:
1. Substitute the values of \(m\) and \(n\) into the expression.
2. Simplify the expression by performing the appropriate arithmetic operations.
Given:
[tex]\[ m = 2 \][/tex]
[tex]\[ n = -4 \][/tex]
Substituting these values into the expression \(-3mn + 4m - 3\):
[tex]\[ -3(2)(-4) + 4(2) - 3 \][/tex]
Step-by-Step Calculations:
1. Calculate the product \(2 \cdot -4\):
[tex]\[ 2 \cdot -4 = -8 \][/tex]
2. Substitute \(-8\) into the expression:
[tex]\[ -3(-8) + 4(2) - 3 \][/tex]
3. Calculate \(-3 \cdot -8\):
[tex]\[ -3 \cdot -8 = 24 \][/tex]
So the expression now reads:
[tex]\[ 24 + 4(2) - 3 \][/tex]
4. Calculate the product \(4 \cdot 2\):
[tex]\[ 4 \cdot 2 = 8 \][/tex]
So the expression now reads:
[tex]\[ 24 + 8 - 3 \][/tex]
5. Perform the addition \(24 + 8\):
[tex]\[ 24 + 8 = 32 \][/tex]
So the expression now reads:
[tex]\[ 32 - 3 \][/tex]
6. Finally, subtract 3 from 32:
[tex]\[ 32 - 3 = 29 \][/tex]
Thus, the value of \(-3mn + 4m - 3\) when \(m = 2\) and \(n = -4\) is:
[tex]\[ \boxed{29} \][/tex]
1. Substitute the values of \(m\) and \(n\) into the expression.
2. Simplify the expression by performing the appropriate arithmetic operations.
Given:
[tex]\[ m = 2 \][/tex]
[tex]\[ n = -4 \][/tex]
Substituting these values into the expression \(-3mn + 4m - 3\):
[tex]\[ -3(2)(-4) + 4(2) - 3 \][/tex]
Step-by-Step Calculations:
1. Calculate the product \(2 \cdot -4\):
[tex]\[ 2 \cdot -4 = -8 \][/tex]
2. Substitute \(-8\) into the expression:
[tex]\[ -3(-8) + 4(2) - 3 \][/tex]
3. Calculate \(-3 \cdot -8\):
[tex]\[ -3 \cdot -8 = 24 \][/tex]
So the expression now reads:
[tex]\[ 24 + 4(2) - 3 \][/tex]
4. Calculate the product \(4 \cdot 2\):
[tex]\[ 4 \cdot 2 = 8 \][/tex]
So the expression now reads:
[tex]\[ 24 + 8 - 3 \][/tex]
5. Perform the addition \(24 + 8\):
[tex]\[ 24 + 8 = 32 \][/tex]
So the expression now reads:
[tex]\[ 32 - 3 \][/tex]
6. Finally, subtract 3 from 32:
[tex]\[ 32 - 3 = 29 \][/tex]
Thus, the value of \(-3mn + 4m - 3\) when \(m = 2\) and \(n = -4\) is:
[tex]\[ \boxed{29} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.